POLITIK HUKUM PENGATURAN KAWASAN SEKITAR TERHADAP KAWASAN WISATA SEBAGAI UPAYA PERLINDUNGAN DAN OPTIMALISASI KAWASAN WISATA DI KABUPATEN TANAH DATAR - Setiawan, Tengku Budi; Artina, Dessy; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Tourism or tourist objects is a source of local revenue in each province inIndonesia. West Sumatra has a lot of potential for natural wealth which is used asa tourist destination. Tanah Datar Regency is one of the areas that has naturalwealth in the form of tourist objects. West Sumatra Province does not yet have aspecial Regional Regulation on Tourism, Likewise with the Tanah Datar RegencyRegulation there is also no regulation on tourism.This type of research can be classified in the type of sociological legalresearch (empirical), because in this study the authors conducted researchdirectly at the location or place under study to provide a complete and clearpicture of the problem under study. The data sources used were primary data andsecondary data. The data techniques in this study were interviews and literaturereview.The conclusions that can be obtained from the research results are First,the legal politics of regulating the surrounding area of tourist areas as an effort toprotect and optimize tourist areas in Tanah Datar Regency are still not fullyimplemented properly. Second, there are several factors inhibiting the formationof regional regulations regarding the surrounding area of tourist areas in TanahDatar Regency. These factors include the absence of mutual understandingbetween the Regional Government of Tanah Datar Regency and DPRD of TanahDatar Regency. and Third, the implication of the formation of regionalregulations on tourist areas as an effort to protect and optimize tourist areas inTanah Datar Regency is an effort to develop and improve the administration oftourism, to develop tourist objects and attractions, both in the form of exploitingexisting tourist objects and attractions. exist or create new objects as touristobjects and have tourist attractions.Keywords: Implementation, Credit Agreement, Business Capital, VillageEconomy Business, Savings and Loans, Community, Pekanbaru.